Formulation strategies for drug delivery of tacrolimus: An overview - Patel, Pranav; Patel, Hitesh; Panchal, Shital; Mehta, Tejal (International Journal of Pharmaceutical Investigation)
Tacrolimus (FK 506) is a potent macrolide lactone immunosuppressive agent used for prophylaxis of organ rejection after transplantation and graft‑versus‑host disease after bone marrow transplantation in patients. Moreover, tacrolimus is a drug of choice in the treatment of atopic dermatitis for decreasing side effects associated with the use of topical corticosteroids. In spite of its success in ensuring graft survival, therapeutic use of tacrolimus is complicated due to its narrow therapeutic index (between 5 and 15 ng/ml). Tacrolimus has a large inter‑/intra‑patient variability in pharmacokinetics profile and a poor oral bioavailability because of its poor solubility, P‑gp efflux, marked pre‑systemic metabolism by CYP3A in the enterocytes and liver first pass effect. Several formulation approaches such as oily solution, solid dispersions, complexation with cyclodextrins, liposomes etc., have been investigated to improve oral delivery of FK 506. In this review, we have discussed various formulation approaches that have been undertaken by various researchers to solve the problems related to the drug delivery of tacrolimus.
Keywords: Bioavailability; drug delivery systems; nanocapsule; self-microemulsifying drug delivery system; tacrolimus